FACTORS INFLUENCING THE IMPLEMENTATION OF PATIENT SAFETY AT RSUD ZUBIR MAHMUD, SENEUBOK BARO, EAST ACEH - Fitriani, Arifah Devi; Mauliyana, Mauliyana; Asriwati, Asriwati (HEARTY, 2026)
Patient safety is a key indicator of hospital service quality, influenced by various individual and organizational factors. The optimal implementation of patient safety requires adequate knowledge, strong motivation, balanced workload, appropriate job design, sufficient work experience, and a fair reward system. This study aimed to analyze the influence of knowledge, motivation, workload, job design, length of service, and rewards on the implementation of patient safety at RSUD Zubir Mahmud. This study employed a quantitative design with a cross-sectional approach. The study population consisted of healthcare workers at RSUD Zubir Mahmud, with a total sample of 85 respondents selected using total sampling technique. Data were collected using a structured questionnaire. Data analysis was conducted using the chi-square test followed by multiple logistic regression. The results showed that knowledge, motivation, workload, job design, length of service, and rewards had a significant effect on patient safety implementation (p < 0.05). Multiple logistic regression analysis indicated that all variables were significant, with rewards identified as the most dominant factor (B = 3.015; p = 0.006; OR = 20.379). This implies that healthcare workers who receive appropriate rewards are approximately 20 times more likely to implement patient safety compared to those who receive less appropriate rewards. In conclusion, patient safety implementation is influenced by both individual and organizational factors, with rewards as the most dominant factor. Hospitals are recommended to develop performance- and safety-based reward systems, enhance healthcare worker training, and manage workload proportionally to strengthen the patient safety culture.